Abiotic stress hormesis: An approach to maintain quality, extend storability, and enhance phytochemicals on fresh produce during postharvest. Issue 6 (31st August 2020) - Duarte‐Sierra, Arturo; Tiznado‐Hernández, Martin Ernesto; Jha, Deepak Kumar; Janmeja, Navina; Arul, Joseph
Abstract: Postharvest losses of whole and fresh‐cut fruits and vegetables cause significant reductions in food availability and an increase in economic losses/damages. Additionally, regulatory agencies are increasingly restricting the postharvest use of synthetic chemicals. This has strengthened the need to develop environmentally friendly approaches to postharvest management, such as utilization of natural compounds, antagonist microorganisms, and treatments with abiotic stresses, among others. The current review focuses on the potential of low doses of abiotic stresses to extend the shelf life, increase the amount of health beneficial phytochemicals, and reduce postharvest losses of fresh produce. The positive effects of the responses to low doses of abiotic stresses are based on a biological phenomenon termed hormesis. Research to develop new technologies to improve postharvest handling of fresh fruit and vegetables as well as minimally processed products is critical. The phenomenon of abiotic stress hormesis in fresh fruit and vegetables shows the potential not only to enhance defense compounds that could reduce diseases during postharvest storage and extend shelf life but also to elevate the content of health‐promoting substances. The beneficial effects of UV‐C hormesis have been extensively investigated in numerous types of fresh produce. However, our knowledge on hormesis exhibited by other abiotic stresses is still limited. Hence, the objective of this review is to discuss the relevance of hormesis for postharvest research by examining whether all abiotic stresses exhibit the phenomenon, its biological significance, the potential application in various commodities, and how it may direct the future of postharvest research.